Slipped-strand mispairing within a polycytidine tract in transcriptional regulator mga leads to M protein phase variation and Mga length polymorphism in Group A Streptococcus - Lei, Benfang; Hanks, Tracey S.; Bao, Yunjuan; Liu, Mengyao (Frontiers in Microbiology, 2023)
The M protein, a major virulence factor of Group A Streptococcus (GAS), is regulated by the multigene regulator Mga. An unexplained phenomena frequently occurring with in vitro genetic manipulation or culturing of M1T1 GAS strains is the loss of M protein production. This study was aimed at elucidating the basis for the loss of M protein production. The majority of M protein-negative (M-) variants had one C deletion at a tract of 8 cytidines starting at base 1571 of the M1 mga gene, which is designated as c.1571C[8]. The C deletion led to a c.1571C[7] mga variant that has an open reading frame shift and encodes a Mga-M protein fusion protein. Transformation with a plasmid containing wild-type mga restored the production of the M protein in the c.1571C[7] mga variant. Isolates producing M protein (M+) were recovered following growth of the c.1571C[7] M protein-negative variant subcutaneously in mice. The majority of the recovered isolates with reestablished M protein production had reverted back from c.1571C[7] to c.1571C[8] tract and some M+ isolates lost another C in the c.1571C[7] tract, leading to a c.1571C[6] variant that encodes a functional Mga with 13 extra amino acid residues at the C-terminus compared with wild-type Mga. The nonfunctional c.1571C[7] and functional c.1571C[6] variants are present in M1, M12, M14, and M23 strains in NCBI genome databases, and a G-to-A nonsense mutation at base 1657 of M12 c.1574C[7] mga leads to a functional c.1574C[7]/1657A mga variant and is common in clinical M12 isolates. The numbers of the C repeats in this polycytidine tract and the polymorphism at base 1657 lead to polymorphism in the size of Mga among clinical isolates. These findings demonstrate the slipped-strand mispairing within the c.1574C[8] tract of mga as a reversible swith controlling M protein production phase variation in multiple GAS common M types.